Effect of elevated temperatures on Tenera oil palm shell concrete on compressive strength and weight loss / Mohammed Fadhil Hama, Mohammed Parvez Anwar and Teck Leong Lau - Hama, Mohammed Fadhil; Anwar, Mohammed Parvez Anwar; Teck, Leong Lau (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
Many studies have been conducted on the use of Dura type oil palm shells (OPS) as a replacement for the conventional aggregates in concrete. However, insufficient studies have been done on a new hybrid type called Tenera OPS by utilising it as a coarse aggregate in concrete. Likewise, just one study has been done on the effect of elevated temperatures on oil palm shell concrete (OPSC) made with Dura OPS. The study of elevated temperatures on concrete is vital to further understand its mechanical strength capability when a structure undergoes a fire incident for a certain amount of time for safety considerations. This study focuses on the compressive strength and weight reduction effects of Tenera OPS-concrete (Tenera-OPSC) when exposed to elevated temperatures at 150, 250, and 350 ºC. In addition, colour change, crack patterns and ultrasonic pulse velocity (UPV) analysis was also evaluated when concrete samples were exposed to elevated temperatures in this study. The results indicate high strength reduction of Tenera-OPSC compared to NWC when exposed to elevated temperatures with a decrease of 50% at 350ºC. A weight reduction of 43% was observed in the Tenera-OPSC type compared to NWC at 350 ºC. Further recommendations have been made for future studies.